Effect of Bulbils Position on Leaf Branches to Plant Growth Responses and Corms Quality of Amorphophallus muelleri Blume - Mastuti, Retno; Harijati, Nunung; Arumingtyas, Estri Laras; Widoretno, Wahyu (The Journal of Experimental Life Science, 2018)
Bulbil (corm leaf) is one material source of vegetative propagation in Amorphophallus muelleri Blume. Based on the position in branches there are two types of bulbil, middle and edge bulbils, which are different in shape and size. It has been reported that bulbil size affected not only the growth response of seedlings and plants but also the quality of the produced corms. Therefore, the objectives of this experiment were to study the effect of bulbils origin on A. muelleri Blume (Porang) growth and the quality of harvested corms. The quality of corms was assessed based on glucomannan and (CaOx) content. Bulbils from the middle and edge of branches were grown in polybag (f 5 cm) containing compost:fertilizer (1:1) mixed media under 40% shade. Each bulbil origin was repeated 8 times. The results showed that growth responses of plant from middle bulbil were significantly better than that from edge bulbil. However, at the harvesting time, the weight and diameter of corms derived from both types of bulbils were not significantly different. The glucomannan and calcium oxalate (CaOx) content of harvested corms grown from middle bulbil tends to be higher than that from edge bulbil.Keywords: branching, calcium oxalate (CaOx), germination, glucomannan, Porang.